Calculation and Analysis of Fractal Descriptors for Protein Amino Acids in Various Conformational States - Grigorev, V.Yu.; Grigoreva, L.D. (Biomedical Chemistry: Research and Methods, 2018)
A series of 20 proteinogenic amino acids was studied. Four types of fractal descriptors for 2 conformational states are calculated: α-helix and 1-strand β-sheet. Based on the analysis of the results obtained, it is established that when the conformational state of the amino acids (α-helix→β-sheet) changes, significant changes in the fractal descriptor Dtot, in the calculation of which all the atoms of the molecule are used, are not observed. However, the more specific descriptors Dval, Dvdw and Dunb, which reflect the aggregate of valence-coupled, van der Waals contact and unbound atoms, respectively, are more sensitive to the conformational transition. The increase Dval, Dvdw and the decrease Dunb values were established for a series of 7 amino acids.